Biosynthesis of guggulsterone in the callus culture of Commiphora wightii. Arnott. bhandari (Burseraceae) - Mishra S.K.; Kumar A. (My University, 2025)
Commiphora wightii is a hard sample which grows very slowly in natural condition but having immense medicinal importance. The propagation of C. wightii through the seed and stem cutting is quite difficult because of its hard nature. Maturity period of sample is also long which unable the availability of plant and produce to industry in right time. Due to over exploitation and slow growing nature it has become endangered also. The study is devoted to ensure the availability of plant and its produce at right time in right quantity and quality through tissue culture technique. Tissue culture technique has been employed for the quick isolation of Guggulsterone which is the active constituent of C. wightii. Callus was induced from nodal segment, leaf and embryo as explants of Commiphora wightii in MS medium supplemented with 2, 4-D and Kn., individually and in combinations. Highest growth of callus (5.78 g) was recorded in the treatment MS + 2, 4-D (5 mg/l) + Kn. (0.5 mg/l). Biosynthesis of guggulsterone was observed in the callus grown in all the treatments with 2, 4-D and Kn., both individually and in combination in MS medium. Quantitative estimation of guggulsterone in cultured callus was studied using TLC and HPLC respectively. Highest guggulsterone content of 0.062% was recorded in the callus cultured in MS + 2, 4-D (5.0 mg/l) + Kn (0.5 mg/l). Callus culture technique may be an important tool to get the Guggulsterone quickly as compared to the nature where it takes around fifteen years. Good quality of Guggulsterone can also be ensured by this technique as compared to the nature. One can get the active constituent (Guggulsterone) without destroying the plant available in nature.